Aedes Distribution and Meteorological Effect on Ovitrap Index in Coastal Area of Besut, Malaysia: An Entomological Study - Awang, Hafizuddin; Mohd Mokhdi, Siti Firdaus; Khalid, Izzati; Othman, Mohd Ridzuan; Mohd Alwi, Nor Alina; Nodin, Nur Hazirah; Laili Nordin, Irda Idura; Jusoh, Mohd Khalil (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Aedes species are a major public health concern due to their ability to be efficient vectors of dengue, and other arboviruses. Ovitrap is an entomological surveillance tool designed to measure the density of Aedes. Ovitraps used for monitoring can detect Aedes mosquito populations, thus acting as an early warning system to prevent dengue outbreaks. Meteorological factor such as temperature and rainfall played great role in affecting the abundance of Aedes mosquitoes. Objective: To assess the presence and abundance of Aedes species, and to determine the correlation of meteorological factors with Ovitrap index. Methods: This cross-sectional study was conducted in coastal area of Besut district, Terengganu state of Malaysia. The study samples were 3120 Ovitraps placed in only occupied premises. Data were collected from Besut Meteorological Department database and respective Ovitrap sentinel stations. The independent variables were environmental temperature and rainfall density, while the dependent variable was Ovitrap index which served as the indicator for Aedes density. Descriptive and correlation analysis were employed for assessing the Ovitrap index, and determining the correlation of Ovitrap Index with temperature, and rainfall distribution. A p-value <0.05 was considered statistically significant. Results: Aedes distribution study showed that Aedes aegypti were more prevalent than Aedes albopictus, with 2,383 larvae of Aedes aegypti being recorded compared to 2,198 larvae of Aedes albopictus. The findings also revealed a significant correlation between the Ovitrap index and temperature (r=0.82, p=0.03) but the analysis showed no statistically significant correlation between the Ovitrap index and the rainfall distribution, with (r=0.15, p=0.62). Conclusion: Temperature plays important role in determining Aedes distribution. The high population of Aedes aegypti highlights the need for proper control actions such as Aedes source reduction. International Journal of Human and Health Sciences Vol. 09 No. 02 Apr’25 Page: 102-106